Idiopathic unilateral third nerve palsy with pupillary sparring in 10-year-old child -a case report. (October 2022) - Khan, Qaisar Ali; Adnan, Sohail; Ahmad, Naseer; Mumtaz, Hassan; Verma, Ravina; shahi, Alishba; Shahi, Ameena; Iram, Sumaira; Baqi, Abdul
Abstract: Introduction and importance: Aneurysm, diabetes mellitus, central nervous system (CNS) infections, pituitary tumors, and ischemia alterations are all potential causes of unilateral oculomotor nerve palsy, a common clinical disease. Case presentation: A 10-year-old child presented with right eyelid ptosis and restricted eye movements associated with diplopia and pain in the right eye. Brain imaging and laboratory tests revealed no obstruction, infection, or hypercoagulable state. The condition was labeled as idiopathic. A patient was diagnosed with ptosis through a sling procedure and after 2 and 4 weeks of follow-up was told he had mild anemia. The patient was prescribed ferrous sulfate 8mg once daily for 4 months and his condition improved. Clinical discussion: Surgery can correct the appearance of crossed eyes, but it seldom restores or significantly improves binocular function. Amblyopia and the loss of binocular vision can occur in children with third nerve palsy due to the excessive angle of incitant strabismus and the resulting ptosis. Conclusion: Patients with idiopathic third nerve palsy must be informed of their prognosis so that they can make an informed decision about whether or not to undergo surgery. Clinical examination is the only way to identify a child's condition and proper investigations and a full history of prenatal and antenatal courses are required. Highlights: Clinical examination is the only way to identify a child with idiopathic third nerve palsy. Proper investigations and a full history of prenatal and antenatal courses are required to exclude congenital and acquired reasons. Patients must be informed of their prognosis so that they can make an informed decision about whether or not to go through with the procedure.